Compound heterozygous SPATA5 variants in four families and functional studies of SPATA5 deficiency - Puusepp, Sanna; Hoffmann, Georg F.; Kotzaeridou, Urania (European journal of human genetics, 2018)
Variants in the SPATA5 gene were recently described in a cohort of patients with global developmental delay, sensorineural hearing loss, seizures, cortical visual impairment and microcephaly. SPATA5 protein localizes predominantly in the mitochondria and is proposed to be involved in mitochondrial function and brain developmental processes. However no functional studies have been performed. This study describes five patients with psychomotor developmental delay, microcephaly, epilepsy and hearing impairment, who were thought clinically to have a mitochondrial disease with subsequent whole-exome sequencing analysis detecting compound heterozygous variants in the SPATA5 gene. A summary of clinical data of all the SPATA5 patients reported in the literature confirms the characteristic phenotype. To assess SPATA5’s role in mitochondrial dynamics, functional studies were performed on rat cortical neurons. SPATA5-deficient neurons had a significant imbalance in the mitochondrial fusion-fission rate, impaired energy production and short axons. In conclusion, SPATA5 protein has an important role in mitochondrial dynamics and axonal growth. Biallelic variants in the SPATA5 gene can affect mitochondria in cortical neurons and should be considered in patients with a neurodegenerative disorder and/or with clinical presentation resembling a mitochondrial disorder.
Gesehen am 18.05.2020